Effect of Host Moieties on the Phosphorescent Spectrum of Green Platinum Complex - Yukiko Iwasaki; Hirohiko Fukagawa; Takahisa Shimizu (Molecules, 2019)
Highly efficient, operationally stable, and pure-color organic light-emitting diodes (OLEDs) are of considerable significance for developing practical wide-color-gamut displays. Further, we have demonstrated the feasibility of an efficient pure green phosphorescent OLED (PHOLED) by employing a narrow-band platinum complex and a top-emitting structure. The utilization of the thermally activated delayed fluorescence (TADF) material as the phosphorescent host is expected to serve as a promising solution for obtaining operationally stable PHOLEDs with high color purity. However, the emission spectrum of the platinum complex in the TADF host exhibits a considerably broad emission spectrum. This study investigates the cause of the spectral change by evaluating the photoluminescence spectra of the platinum complex in various hosts exhibiting different molecular structures. The triazine unit in the host material was observed to result in exciplex formation between the lowest unoccupied molecular orbital (LUMO) of the host and the highest occupied molecular orbital (HOMO) of the platinum complex. Therefore, the TADF material that sterically hinders the triazine unit is considered to be suitable to prevent both exciplex formation and spectral broadening.